An intensive course in Sindhi - Kanhaiyalal Lekhwani (Central Institute of Indian Languages Mysore, 1997)
An Intensive Course in Sindhi is for adult learners learning Sindhi as a second language. In this book English, Arabic and Devanagari Scripts are used.
Keywords: Sindhi; Intensive Course; Sindhi; Sindhi; English